Rapid increases in fine root biomass and production following cessation of anthropogenic disturbances in degraded forests. (30th January 2018) - Feng, Chun; Wang, Zhe; Zhu, Qi; Fu, Songling; Chen, Han Y. H.
Abstract: Despite the critical importance of fine roots (FRs, ø ≤ 2 mm) in terrestrial carbon and nutrient cycling, we know little about FR dynamics following cessation of anthropogenic disturbances in degraded forests. We hypothesized that (a) FR biomass and production increase rapidly following cessation of anthropogenic disturbances and then decline with stands ageing and (b) FR mortality and turnover are highest in degraded forests due to recurring disturbances. We used a replicated chronosequence to examine the effect of cessation of disturbances on FR dynamics by sampling stands with ongoing anthropogenic disturbances such as fuelwood collection and domestic animal grazing and stands after 6, 11, 21, and 31 years prohibited from anthropogenic disturbances using mountain closure in subtropical forests of eastern China. We found that FR biomass and production increased rapidly from stands without closure to those after 6 years of closure. As stands overmatured, biomass and production declined and stabilized thereafter. Both FR mortality and turnover decreased over time from stands without closure and after 6 years of closure to those closed for longer times. Biomass, production, and mortality correlated positively with the proportion of bamboo, overstorey species richness, and herb layer cover, whereas turnover rate correlated negatively with stand density and basal area. Our results show evidence for rapid increases in FR biomass and production following cessation of anthropogenic disturbances. Our results suggest that stand‐level FR dynamics following mountain closure are influenced by changes in overstorey species composition and richness and understorey vegetation cover.